Psychopathology and coping in recently diagnosed HIV/AIDS patients- the role of gender (2003)
Although there is growing literature on the psychological responses to and the psychopathology associated with HIV/AIDS, few investigations have focused on the role of gender. This study compared psychiatric morbidity, coping responses, and disability in male and female outpatients recently diagnosed with HIV/AIDS. Method. One hundred and forty-nine patients (44 male, 105 female) with HIV/AIDS (mean ± standard deviation (SD) months since diagnosis 5.8 ± 4.1) attending an infectious diseases clinic at Tygerberg Hospital, Cape Town, were evaluated. Subjects were assessed using the MINI International Neuropsychiatric Interview (MINI), the Carver Brief COPE, and the Sheehan Disability Scale. In addition, negative life events and risk behaviours were evaluated. Results. Fifty-six per cent of patients were diagnosed with a psychiatric disorder, most commonly major depression (34.9%), dysthymic disorder (21.5%), post-traumatic stress disorder (14.8%), and alcohol dependence (10.1 %). There were no significant gender differences in the prevalence of mood disorders in the sample. Men, however, were more likely than women to meet diagnostic criteria for alcohol abuse or dependence, and to engage in certain risky sexual behaviours. Women were more likely to suffer from post-traumatic stress disorder, and to use coping strategies of planning and religion to deal with the illness. There were no significant gender differences in disability. Conclusion. Psychiatric disorders are common in recently diagnosed HIV/AIDS patients in South Africa. Clinicians should be aware of the high prevalence of mood disorders in both men and women, and of gender-different responses such as increased alcohol and substance use and more risky sexual behaviour in men.